Collection and dissemination of data from environmental monitoring systems in estuaries - Garel, Erwan (2018)
Environmental monitoring stations providing high frequency data over a multiyear time frame are not common in estuaries. These systems are designed to record extended timeseries at high frequency that are of great value for decision makers and the scientific community. However, the continuous acquisition of good quality data at estuaries is generally challenged by harsh environmental conditions. This contribution describes the main issues for continuous valid data (water quality and currents) acquisition in 2008-2014 with a monitoring station deployed at the Guadiana Estuary and how both near real-time and post-processed data were disseminated using web interfaces